2014
DOI: 10.1093/cercor/bhu093
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Tract Integrity Contributes to Pattern Separation Performance Across the Lifespan

Abstract: Accurate memory for discrete events is thought to rely on pattern separation to orthogonalize the representations of similar events. Previously, we reported that a behavioral index of pattern separation was correlated with activity in the hippocampus (dentate gyrus, CA3) and with integrity of the perforant path, which provides input to the hippocampus. If the hippocampus operates as part of a broader neural network, however, pattern separation would likely also relate to integrity of limbic tracts (fornix, cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
86
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 73 publications
(95 reference statements)
16
86
0
Order By: Relevance
“…Specifically, it appears that the discrimination between targets and similar lures in the old/new test format most closely resembles the A-A’ test format. Previous studies from our lab and others have revealed an age-related impairment in the discrimination between targets and similar lures across a variety of test formats, including old/similar/new (Toner et al, 2009; Yassa et al, 2011a, 2011b; Stark et al, 2013, 2015; Bennett et al, 2015), old/new (Stark et al, 2015), and old/new with confidence ratings (Stark et al, 2015). Moreover, these effects maintained across a variety of encoding conditions—e.g., incidental encoding, intentional encoding, continuous recognition (Stark et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Specifically, it appears that the discrimination between targets and similar lures in the old/new test format most closely resembles the A-A’ test format. Previous studies from our lab and others have revealed an age-related impairment in the discrimination between targets and similar lures across a variety of test formats, including old/similar/new (Toner et al, 2009; Yassa et al, 2011a, 2011b; Stark et al, 2013, 2015; Bennett et al, 2015), old/new (Stark et al, 2015), and old/new with confidence ratings (Stark et al, 2015). Moreover, these effects maintained across a variety of encoding conditions—e.g., incidental encoding, intentional encoding, continuous recognition (Stark et al, 2015).…”
Section: Discussionmentioning
confidence: 92%
“…Through extensive testing, we have previously demonstrated that the lures have a controlled range of false alarm rates when used during recognition tests (Yassa et al, 2011a; Stark et al 2013; 2015). In addition, performance on these similar lures is sensitive to hippocampal damage (Kirwan et al, 2012), aging (Stark et al, 2013; 2015; Toner et al, 2009) and to the age-related changes in both the activity of the dentate gyrus and CA3 subfields during aging (Yassa et al, 2011b), and to disruptions of hippocampal circuitry (Yassa et al, 2011b; Bennett et al, 2015). Together, these findings demonstrate the viability of this task as a sensitive and appropriate measure of age-related memory change and of hippocampal function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many studies have shown that age-related differences in behavioral and motor task performance are mediated by age-related variations in DWM DTI metrics (Bucur et al, 2008;Hedden et al, 2014;Holtrop et al, 2014;Jacobs et al, 2013;Kerchner et al, 2012;Madden et al, 2009). Nevertheless, in several recent studies, the relationships between DWM diffusion metrics and cognitive ability is attenuated or completely lost after accounting for the effects of age (Bennett et al, 2014;Borghesani et al, 2013;Koch et al, 2013;Lockhart et al, 2012;Metzler-Baddeley et al, 2011;Salami et al, 2012). This heterogeneity of results may be attributed to a number of factors such as the DWM tracts studied, the metrics reported (e.g., FA, MD, or other metrics), the cognitive tests used, the sample size, or the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, human studies that have assessed spatial discrimination have also used screen-based presentation of stimuli, requiring subjects to gauge the position of shapes or pictures of objects on the screen (Stark et al 2010;Holden et al 2012;Reagh et al 2014Reagh et al , 2016, which is quite different from using real world spatial representations and/or path integration to guide discrimination. Nonetheless, studies using this type of stimulus presentation have found age-associated discrimination deficits to be correlated with altered CA3 and dentate gyrus activity (Yassa et al 2011a,b;Bakker et al 2012), and more specifically with loss of integrity of perforant path inputs from the entorhinal cortex to the hippocampus and dentate gyrus (Bennett et al 2015;Bennett and Stark 2016). The extent to which prefrontal cortical input is also necessary and engaged by these behaviors in humans will need to be explored.…”
Section: Spatial Memory and Spatial Discrimination Abilities: Implicamentioning
confidence: 99%